Marriage Aspects Of Minangkabau Matrilineal Systems In Hamka’s Tenggelamnya Kapal Van Der Wijck - SYAMSUL BAHRI (BAHAS, 2014)
This study explores the cultural elements found in the literary work of Tenggelamnya Kapal Van Der Wijck in the  form of Novel written by Buya Hamka. It utilizes an extrinsic approach in which there are some interpretations and explanations about cultural elements in Hamka’s  Tenggelamnya Kapal Van Der Wijck. It describes the aspects of marriage based on Minangkabau custom especially practiced in Batipuh, West Sumatera that still hold fast to the tradition and culture very much concerned to the female (matrilineal) lineage. There are several elements of culture on the marriage of Minangkabau matrilineal systems in the novel of  Tenggelamnya Kapal Van Der Wijck, namely ; 1.Mamak (mother’s brother) whether he is eldest or youngest ,he has a huge role and responsibility to preserve the tradition of Minangkabau Matrilineal systems in the family of Minangkabau,West Sumatera and he will bring the matters of custom     into the meeting of Niniak Mamak .2. If a man wants to marry a woman, Niniak Mamak from the man directly has to come to the family of the women asking about the marriage . 3. Someone who has a right to receive or deny a proposal of marriage is not the woman or even the parents or aunt (mandeh) of the woman. Mamak (uncle), mother’s brother has a big role for it and then he brings it into the meeting ofNiniak Mamak in order to get a decision to receive or not. 4. Mamak (uncle) of a Minangkabau woman will just receieve a man from Minangkabau who has a clan from lineage of mother (Piliang,Sikumbang,or Chaniago etc ) will be accepted being a husband for niece . Mamak will not accept a mixed race  man  to be a husband for a niece in the conservative society of Minangkabau Matrilineal systems,West Sumatera         Keywords: Marriage, Matrilineal System, Minangkabau, Tenggelammnya Kapal Van Der Wijck